Note—A Comment on Keeney's Group Utility Axioms - McClain, John O. (Management Science, 1977)
Keeney has described a set of axioms which allows one to merge individual utility functions using a linear combination [Keeney, Ralph L. 1976. A group preference axiomatization with cardinal utility. Management Sci. 23 140–145]. This is a very handy result, especially because the linear combination is probably the most easily studied of all possible methods. This comment is intended to call attention to three concepts which aid in determining and interpreting the weights obtained and studying the structure of the group's preferences. These concepts have been illustrated in [McClain, John O., Vithala R. Rao. 1974. Tradeoffs and conflicts in evaluation of health system alternatives: methodology for analysis. Health Services Res. (Spring) 35–52].